Synthesis and Characterization of Polyoxometallate Compounds of Amine and Phosphine with Molybdovanadophosphoric Acid in Keggin Type - Gumgum, Bahattin; Akba, Osman; Baysal, Akin; Hamamci, Candan (Asian Journal of Chemistry, 2010)
Four novel compounds were synthesized by the reaction of tertiary amines (triphenyl amine, triethyl amine, tributyl amine) and triphenyl phosphine with freshly prepared molybdovanadophosphoric acid (H4PMO11VO40.32H2O). The products were characterized by elemental analysis, spectroscopic techniques (UV, IR, ICP-AES) and thermal analysis (TG/DTA). The experimental data indicated that the synthesized compounds retain the Keggin structure.